Proceso de atención de enfermería en recién nacido con diagnóstico de síndrome de abstinencia neonatal. - Rizzo Alfonso, Stefany Belén (2023)
Today the problem of substance abuse is growing in the world, this favors it to be a risk factor for withdrawal of the newborn, the mother administers this drug and through the blood that she shares with the baby in the placenta makes him dependent, when he is born and as the hours go by, a series of withdrawal reactions occur, this ifluences the type of drug, the last time he consumed and the weeks of premature or full-term gestation, with signs of irritability (crying a lot ), hyperactive reflexes, vomiting or diarrhea, sweating, and variable temperature. It is necessary to make a good assessment and detect the problem early, minimizing the consequences on the fetus as much as possible. The present clinical case was carried out in a newborn of 39.6 weeks of gestation with neonatal abstinence syndrome at the HOSPITAL GENERAL LIBORIO PANCHANA SOTOMAYOR in the neonatology area, being the (SAN) one of the most frequent complications that can occur in newborns of mothers with a history of substance use this The primary goal is to put into practice the care process. Nursing in the newborn who is in neonatal abstinence. An exhaustive assessment is made to the newborn by means of the patterns functions of MARJORIE GORDON through which it was possible to decide the patterns that were altered and, because of these discoveries, make a correct nursing care process to execute it successfully and achieve the improvement of the newborn during his hospital stay.